Developing Language Teachers with Exploratory Practice Innovations and Explorations in Language Education (Springer International Publishing, 2018)
'This volume demonstrates how teachers, teacher educators, and curriculum developers "puzzle" their way through a range of classroom-relevant topics related to their practice. The inspirational chapters provide illustrative examples of how to go about Exploratory Practice (EP) in different contexts and for different purposes. Additionally, mentors, with whom the practitioners collaborated in a series of activities and workshops, provide relevant theoretical grounding about EP. Altogether, the book makes an excellent contribution to the growing work on EP in various regions around the world.' -Gary Barkhuizen, University of Auckland, New Zealand This edited collection explores the use of Exploratory Practice (EP) by language teachers in classrooms. Written by practitioners, the chapters showcase unique examples of each principle of EP, with topics ranging from mentoring practitioner researchers, to teaching and learning in EAP, and investigating curriculum development in language teaching programs. The book provides example EP studies and gives voice to practitioners' experiences of the challenges they experienced as well as the benefits. Examples include tackling intercultural communication in linguistically and culturally diverse classrooms; pedagogy and curriculum design in language teaching; explorations of continuing professional development in language education. In doing so, it offers tools that can be transferred to other classroom contexts and used to aid teacher development. The concluding chapter highlights critical aspects of Exploratory Practice which emerge in the studies and examines how practitioners advanced their understandings. This book will appeal to those working in Applied Linguistics, TESOL research, as well as language teachers and teacher educators. Kenan Dikilitaş is Assistant Professor in the ELT department at Bahçeşehir University, Turkey. His primary research interests include English language teacher education and teacher professional development. He has published articles and books on action research and teacher research, and conducted several teacher research projects with local teachers. Judith Hanks is Associate Professor at the School of Education, University of Leeds, UK. Her research interests lie in the areas of Exploratory Practice (a form of practitioner research), language learning and teacher education, continuing professional development, and intercultural issues in language education. .